Differential mRNA expression of TACR1 after ischemic peritoneal trauma: a pilot animal study - Krämer, Bernhard; Wallwiener, Markus (Archives of gynecology and obstetrics, 2012)
Purpose: Experimental trial in an in vivo animal model in the laboratory facilities of a university department of obstetrics and gynecology and a microarray facility using seventeen female Wistar rats to investigate the regional expression level of TACR1 at specific locations in the peritoneum in a rodent animal model of post-operative adhesions.Methods: Peritoneal adhesions were induced by the placement of three unilateral ischemic lesions. A time course experiment was performed to identify when adhesions form in this model to determine the optimal time for tissue harvesting. To this effect, second look analysis for adhesion scoring occurred after day 1, 3 and 5. Eighteen tissue samples from the adhesiogenic lesions and the contralateral non-adhesiogenic peritoneum were harvested from n = 3 animals at day 3 for quantitative real-time PCR analysis. Results: After 1 day, no adhesions were macroscopically detectable. After 3 days, adhesions were detectable which could be separated easily by gravity. After 5 days, all animals had formed adhesions and strong traction was required for adhesiolysis. The adhesions always formed to the ischemic part of the lesions. Quantitative PCR analysis after 3 days demonstrated down-regulation of TACR1 mRNA in the adhesiogenic peritoneum of the lesions compared to non-adhesiogenic peritoneum on the contralateral side. This difference was statistically highly significant (p < 0.01). Conclusions: In the ischemic lesion model of adhesiogenesis, TACR1 is differentially expressed between adhesiogenic peritoneum and non-adhesiogenic peritoneum at the time-point of adhesion formation.
Published online: 12 August 2011
Gesehen am 08.11.2018